Pelatihan Manajemen Konflik Pada Pengurus Koperasi Setia Bhakti Wanita Surabaya - Tuty Lindawati; Julius F Nagel; Ani Suhartatik; Arini Arini; Ninuk Muljani (LPPM, Universitas Katolik Widya Mandala Surabaya, 2019)
This community service aims to provide additional insight into how conflict management is aimed at administrators of loyal bhakti women cooperatives in Surabaya. Increasing the capability of members and increasing the level of effectiveness of conflict handling in cooperatives are the goals of this community service activity. 38 administrators and 9 administrators who also act as supervisors. The total number of participants of the Surabaya Setia Bhakti Wanita Surabaya cooperative community service was 47 people who participated in this activity. Through a workshop and interactive discussion this activity was held. Time limitation is the main drawback in this activity.